The role of Electronic human resources management practices in the sustainability of knowledge capital - الزبيدي, غني دحام; ناظم, محمد حسين (Journal of Economics and Administrative Sciences, 2019)
Abstract:The aim of the research is to highlight the role of electronic human resources management practices in the sustainability of knowledge capital as one of its success factors, as well as the diagnosis and interpretation of the relationship between research variables and their dimensions. The research problem is that the University of Babil implements some electronic human resources management practices not in a complete way, The level of its application and the problems it faces, as well as the extent to which these practices reflect the knowledge capital and sustainability in the university, and highlights the importance of research as it is concerned with the electronic aspects and achieve the competitive advantage of organizations by reducing costs, and adopts the questionnaire as a tool for collecting data and information, 150 questionnaires are distributed, 135 of which are validated and 15 are excluded. The study has two main hypotheses that are subjected to statistical tests. The researcher used the statistical program SPSS and a set of statistical methods for data analysis, The standard deviation, the Spearman correlation coefficient, the coefficient of variation, and the simple regression equation). The main conclusions are the University of Babil adopts some practices of human resources management electronically and this is evident through the results of practical analysis. The most important recommendations are the development of appropriate training plans and programs to educate employees about the academic concepts of the research variables, the positive results of their use, and their cost advantages of reducing costs and maintaining the working environment.